Mareva injunctions under Singapore law - CHONG, Adeline (Institutional Knowledge at Singapore Management University, 2018)
Whether the Singapore court has the jurisdiction or power to grant a Mareva injunction in aid of foreign court proceedings was recently considered by the Singapore High Court in PT Gunung Madu Plantations v Muhammad Jimmy Goh Mashun [2018] SGHC 64. Both plaintiff and defendant were Indonesian and the claim related to alleged breaches of duties which the defendant owed to the plaintiff. The plaintiff had obtained leave to serve the writ in Indonesia on the defendant. The defendant thereupon applied, inter alia, to set aside service of the writ and for a declaration that the court has no jurisdiction over him. In response, the plaintiff applied for a Mareva injunction against the defendant in respect of the defendant’s assets in Singapore. The plaintiff had, after the Singapore action was filed, commenced actions in Malaysia and Indonesia covering much the same allegations against the defendant.